2019
DOI: 10.1093/brain/awz201
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic perspective on CSF-mediated neurodegeneration in multiple sclerosis

Abstract: Multiple sclerosis is an autoimmune demyelinating disorder of the CNS, characterized by inflammatory lesions and an underlying neurodegenerative process, which is more prominent in patients with progressive disease course. It has been proposed that mitochondrial dysfunction underlies neuronal damage, the precise mechanism by which this occurs remains uncertain. To investigate potential mechanisms of neurodegeneration, we conducted a functional screening of mitochondria in neurons exposed to the CSF of multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…4 E). This finding supports previous studies on the importance of this lipid in neurodegeneration 9 . The remaining two hexosyl-ceramides [DiHexCer(d18:1/18:2), and DiHexCer(d18:1/18:3)] were less abundant in PPMS patients compared to controls (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…4 E). This finding supports previous studies on the importance of this lipid in neurodegeneration 9 . The remaining two hexosyl-ceramides [DiHexCer(d18:1/18:2), and DiHexCer(d18:1/18:3)] were less abundant in PPMS patients compared to controls (Fig.…”
Section: Resultssupporting
confidence: 93%
“…4E). This finding supports previous studies on the importance of this lipid in neurodegeneration 9 . The remaining two hexosyl-ceramides 4F) and a positive correlation was found between its levels and MRI metrics of decreased CblWMV at the one-year follow-up.…”
Section: Controlssupporting
confidence: 93%
“…Recent research has revealed important correlation of mitochondrial dynamics and the pathophysiology of brain diseases, as Alzheimer's. Disease (AD), Parkinson's Disease (PD) and Multiple Sclerosis (MS) (11)(12)(13). Disturbances in mitochondrial dynamics may influence many cellular and molecular pathways, as calcium-dependent immune activation, transcription factors phosphorylation, cytokine secretion, organelle transference and even cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) from MS patients significantly alters neuronal mitochondria shape and glucose uptake, coupled with a suppression of mitochondria complexes I, III, and IV, as well as reduced ATP production. The authors attribute this to CSF exosomes containing ceramides and the phosphorylation of dynamin-related protein (DRP)1 [43]. Such data link to previous studies showing suboptimal mitochondria functioning in MS and indicate an attempt to increase glycolysis under challenge [44].…”
Section: Ms Pathophysiologymentioning
confidence: 65%